Hollywood youth dystopias: sociocultural projections of contemporaries' fear about future worlds / Голливудские молодежные антиутопии: социокультурные проекции страха современников по поводу будущих миров - Ilya Suzumov / Илья Александрович Сюзюмов (Индустрии впечатлений: Технологии социокультурных исследований)
The article deals with the phenomenon of anti-utopian works of the 21st century, associated with a qualitative expansion of the projections of the fear of contemporaries on the world of the future. The relevance of the topic is due to both an increase in the number of dystopian works, and an increase in mass consumer demand for visualized dystopias, an increase in the importance of dystopias in the ideological development of modern socio-cultural space. The dystopias filmed by Hollywood, which are gaining more and more consumer popularity, make it possible to analyze the projected individual and collective fears, identify the main signs of “unwanted” dystopian worlds for the authors, and also explore the ideas broadcast by their creators to the masses. The article discusses the most obvious fears projected by Hollywood, determines the causes of their occurrence and the degree of their unconsciousness, fixes the main socio-political goals and ideological scenarios for the introduction of identified fears into the spaces of other socio-cultural traditions. The characteristics of the reasons for the evolution and transformation of fears inherent in post-war generations are given, the basic reasons for their changes and the significance for dystopia as a genre are determined. An analysis is made of visualization techniques and mental and ideological impact on the consumer used in the creation of anti-utopian films. The article directly relies on the analysis of modern Hollywood youth dystopias: The Hunger Games, Divergent, The Maze Runner, which not only have traditional literary bases, but are also supplemented by large-scale and box office film versions. В статье рассмотрен феномен антиутопических произведений XXI века, связанный с качественным расширением действия проекций страха современников на мир будущего. Актуальность темы обусловлена, как увеличением количества антиутопических произведений, так и ростом массового потребительского спроса на визуализированные антиутопии, повышением значимости антиутопий в идеологическом освоении современного социокультурного пространства. Экранизированные Голливудом антиутопии, обретающие все большую потребительскую популярность, позволяют провести анализ спроецированных индивидуальных и коллективных страхов, выявить основные признаки «нежелательных» для авторов антиутопических миров, а также исследовать идеи, транслируемые их создателями в массы. В статье рассматриваются наиболее явные спроецированные Голливудом страхи, определяются причины их возникновения и мера их бессознательности, фиксируются основные социально-политические цели и идеологические сценарии внедрения выявленных страхов в пространства иных социокультурных традиций. Дается характеристика причин эволюции и трансформации страхов, свойственных послевоенным поколениям, определяются базисные причины их изменений и значимость для антиутопии как жанра. Проводится анализ приемов визуализации и ментально-идеологического воздействия на потребителя, используемых при создании антиутопических кинокартин. Статья непосредственно опирается на анализ современных голливудских молодежных антиутопий: «Голодные игры», «Дивергент», «Бегущий в лабиринте», имеющих не только традиционные литературные основы, но и дополненных масштабными и кассовыми киноверсиями.